Talking about PrEP: South African adolescent girls and young women's communication about pre-exposure prophylaxis with partners, parents and peers - Sindi, Babalwa; Duby, Zoe; Jonas, Kim; Bergh, Kate; Lotvonen, Mari; Mathews, Catherine (Frontiers in Reproductive Health, 2025)
BackgroundHigh rates of HIV among adolescent girls and young women (AGYW) persist as a critical public health issue in South Africa. Pre-exposure prophylaxis (PrEP) is a promising HIV prevention method for reducing new infections. To enable AGYW to access, make decisions about, and effectively use PrEP, they require support from partners, parents, and peers, which is dependent on effective PrEP communication. This study examined barriers to, facilitators of, and outcomes of effective PrEP communication between AGYW and their partners, parents/caregivers and peers.MethodsThis paper presents data from a qualitative study conducted in seven South African provinces. A total of 68 in-depth interviews were conducted with AGYW aged 15–24 years. Audio recordings of interviews were transcribed and translated into English, and preliminary thematic analysis of transcripts was conducted by a team of analysts. A second phase of analysis focusing on PrEP communication was conducted to further extract meaning from the coded data.FindingsThe barriers to effective communication between AGYW and their partners included a lack of accurate information about PrEP, fear that partners would think that they did not trust them, and stigma related to PrEP's association with promiscuity and PrEP being mistaken for HIV treatment. The barriers hindering PrEP communication between AGYW and their parents were similar, including fear of judgement, and PrEP stigma related to assumptions of promiscuity. Open communication was a facilitator of effective PrEP communication between AGYW and partners, parents and peers. The benefits and outcomes of effective PrEP communication included increased knowledge about PrEP, motivation to use PrEP, PrEP use and continuation on PrEP.ConclusionsTo address barriers to effective PrEP communication, community PrEP awareness campaigns and education programmes are needed and should include men, parents and peers. Increased knowledge and awareness of PrEP is likely to result in reduced PrEP stigma, improved PrEP communication and subsequent uptake.